Eco-luxury: Making sustainable drugs and cosmetics with Prosopis cineraria natural extracts - Giustra, Marco; Cerri, Federico; Anadol, Yaprak; Salvioni, Lucia; Antonelli Abella, Tatiana; Prosperi, Davide; Galli, Paolo; Colombo, Miriam (Frontiers in Sustainability, 2022)
Climate change associated to global warming is a major threat of the 21st century, threatening ecosystems through uncontrolled temperature rises, drought, lack of water with strong impact on productivity, economy, and worldwide life well-being. In most cases, the poor regions of the planet suffer from lack of exploitable resources deriving from natural reserves. Thus, wild vegetables able to grow in deserted areas, are attracting increasing attention due to their beneficial properties. Among them, Prosopis cineraria has been recently recognized as a potential source of raw materials for agri-food and pharmaceutics still poorly valued. P. cineraria occurs in most of the world’s hot arid and semi-arid regions as native or introduced species and thanks to the multiple properties could be exploited for medical, food, and, more recently, in different growing productivity fields like luxury. The use of actives-rich natural sources offers clear advantages over synthetic compounds in terms of process and product eco-sustainability. In this manuscript, we review the main properties and potential applications of P. cineraria aiming to promote the scientific interest toward the development of innovative approaches in several productive fields, including pharma and cosmetics, exploiting the versatility of materials that can be extracted from the various parts of the plant and discuss commercialization opportunities of the plant to support biodiversity and sustainability. In conclusion, P. Cineraria turns out to be a plant able to grow in hostile environments, already providing nutrients for populations of Western Asia and the Indian subcontinent and possibly translatable to poor arid regions.